PELAKSANAAN FUNGSI PETUGAS LAPANGAN KELUARGA BERENCANA (PLKB) DALAM MENINGKATKAN JUMLAH PESERTA KB DI KELURAHAN LANGGINI KECAMATAN BANGKINANG KABUPATEN KAMPAR TAHUN 2011-2012 - INDRAWATI, WULAN; MUCHTAR, ERMAN (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The family planning program (kb) inurban village, sub-district and kampar bangkinang langgini family planning should be conducted by officers located in the organizational structure and work procedures of the local district kampar kampar is on the region regulation no. 6 / 2010.Officer for the family planning program is in office in the centre of the function of the article 106.The study is done in kelurahan langgini due to the lack of community participation for kb is the policy of the government the lack of the ability to communicate in the field of energy ( pkb ) in the socialization of family planning, and the social impact in understanding of cultural and religious family.It ' s a problem with the performance of the house why plkb in urban village to village / sub-district in langgini bangkinang kampar in 2011-2012 not run optimally.The purpose of this research is to find out ( plkb ) on the implementation of the program participants, a member of the family, and know nothing of all constraints plkb job itself.The concept was a concept to be used by edward iii who suggested the concept of which there are four things which are important in communication resources, the disposition and the bureaucracy.Based on the results of the research at this skripsi the authors conclude that it is not enough to lack the officer for the family planning program by the government is keikut sertaan to join kb program in the community.And advice as one who is in the improvement of co-operation between harapkannya to the public to support the officer for the family planning program(kb).Keywords: implementation, participation, and public policy